2017
DOI: 10.31351/vol20iss2pp59-65
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Wound Infections and the Antimicrobial Susceptibility in Baghdad Hospitals

Abstract: Nosocomial infections are one of the most important causes of mortality and morbidity in hospitals. These are major public health problems worldwide, but particularly in developing countries. The purpose of this research was to analyze the frequency of the microorganisms in the specimens taken from the surgical wounds, and to examine antimicrobial susceptibility for some isolates . Wound swabs were examined from June 2010 to January 2011. The isolates were identified by conventional methods, antimicrobial susc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The previous investigation elucidates that P. mirabilis was detected in the wound swab samples collected from diabetic foot ulcer patients in Baghdad [9]. Another study [13] found that the occurrence of P. mirabilis infections was almost 14% of all 80 all-positive bacterial infections detected in surgical wound samples.…”
Section: Discussionmentioning
confidence: 96%
“…The previous investigation elucidates that P. mirabilis was detected in the wound swab samples collected from diabetic foot ulcer patients in Baghdad [9]. Another study [13] found that the occurrence of P. mirabilis infections was almost 14% of all 80 all-positive bacterial infections detected in surgical wound samples.…”
Section: Discussionmentioning
confidence: 96%
“…The study was a cross-sectional descriptive survey conducted among 260 HCWs using convenient sampling technique [1], [2], [3], [4]. The HCWs studied were surgeon doctors, assistant surgeons, nurses, laboratorians, and dentists in Baghdad Teaching Hospital and Ghazy Al-Hariri Hospital.…”
Section: Methodsmentioning
confidence: 99%
“…The aim of the study was to assess the knowledge, attitude, and practice of healthcare workers toward needle stick injuries using a guided questionnaire in Baghdad Teaching Hospital and Ghazy Al Hariri Hospital in 2020, Determine the prevalence of needle stick injuries among healthcare workers in Baghdad Teaching Hospital and Ghazy Al Hariri Hospital in 2020, assess the predisposing factors of needle stick injuries, and to assess hepatitis B immunization status in the study group [3], [9], [10].…”
Section: Aimmentioning
confidence: 99%
See 2 more Smart Citations